Preparation and Stabilization of High Molecular Weight Poly (acrylonitrile-co-2-methylenesuccinamic acid) for Carbon Fiber Precursor - Shuxian Zhang (MDPI AG, 2021)
Bifunctional comonomer 2-methylenesuccinamic acid (MLA) was designed and synthesized to prepare acrylonitrile copolymer P (AN-co-MLA) using mixed solvent polymerization as a carbon fiber precursor. The effect of monomer feed ratios on the structure and stabilization were characterized by elemental analysis (EA), Fourier transform infrared spectroscopy (FTIR), gel permeation chromatography (GPC), X-ray diffraction (XRD), proton nuclear magnetic (1H NMR), and differential scanning calorimetry (DSC) for the P (AN-co-MLA) copolymers. The results indicated that both the conversion and molecular weight of polymerization reduce gradually when the MLA content is increased in the feed and that bifunctional comonomer MLA possesses a larger reactivity ratio than acrylonitrile (AN). P (AN-co-MLA) shows improved stabilization compared to the PAN homopolymer and poly (acrylonitrile-acrylic acid-methacrylic acid) [P (AN-AA-MA)], showing features such as lower initiation temperature, smaller cyclic activation energy, wider exothermic peak, and a larger stabilization degree, which are due to the ionic cyclization reaction initiated by MLA, confirming that the as-prepared P (AN-co-MLA) is the potential precursor for high-performance carbon fiber.